PTE (Pearson Test of English) General Skills Boosters. Level 4: Students' Book - Baxter S. Steve (Harlow, Pearson, 2011)
PTE General is a comprehensive and coherent assessment programme that covers all the Common European Framework (CEF) levels. It gives test takers the opportunity to identify their strengths, and track improvement and success over time. PTE General is used by test takers who are looking for an English test that allows them to build a portfolio of their language ability for travel, further education or to improve their employment prospects. Available for Levels 2 to 5 of PTE General, the Skills Boosters are a series of practice tests with guidance which offer complete preparation for PTE General. This Skills Booster provides five complete practice tests which follow the format of the exam so that you can/ Understand the features and format of the test. Learn how to respond to each item type. Practice answering authentic questions prepared by the test developers. Practice items for each of the language skills: reading, writing, Focus on the language related to the themes of the test with vocabulary and grammar practice sections. Study new words and phrases for each unit with the Glossary. Improve test-taking strategies with test tips, the writing guide and model answers for each exam task type.